(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
In recent years, digital technologies have rapidly developed, and social networks have become an integral part of the lives of school-aged children. This article analyzes the impact of social networks on children’s mental health, including risks such as online bullying, social isolation, and the emergence of psychological problems. The article emphasizes the importance of cooperation among all sectors of society to ensure the safe use of social networks.